Ecological risk assessment of organochlorine pesticide residues in sediment samples from Lake Tana and Hayqe in Northwest Ethiopia - Tarekegn Fentie Yimer; Dessie Tibebe Ayele; Yezbie Kassa Brihanu; Mulugeta Legesse Akele; Marye Mulugeta Kassaw; Addis Kokeb Alemu; Dereje Yenealem Ayitegeb; Tsegaye Adane Birhan; Zerubabel Moges Amare; Agmas Amare semegn; Marie Yayinie Erikihun; Amogne Wendu Digisu; et al. (Emerging Contaminants)
In most developing countries, including Ethiopia, the excessive use of toxic and persistent pesticides for agricultural and malaria control purposes poses a significant challenge. This study focuses on evaluating the concentration and ecological risks associated with organochlorine pesticides (OCPs) in the sediments of Lake Tana and Hayqe. Employing a laboratory-based cross-sectional approach, the residues of OCPs in sediment samples were extracted using the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method, followed by dispersive solid phase extraction cleanup (d-SPE) techniques and analyzed for 18 OCPs by gas chromatography coupled to tandem mass spectrometry (GC-MS). The risk Quotient (RQ) method was adopted for ecological risk assessments by using fish, daphnia, and algae as indicators. The concentration of OCPs ranged from 10.11 to 125.65 μg/kg and 10.96–45.17 μg/kg in Lake Tana and Hayqe, respectively. There was a statistically significant difference in the mean concentration of OCPs across the sampling sites in Lake Tana. Deltamethrin and lindane exhibit comparatively lower concentrations among the OCPs, whereas endrin, DDT, and their metabolites were the predominant pesticides in the study area, exceeding WHO and USEPA residue limits, except for endosulfan. Risk Quotient values ranged from 0.006 to 865.4 in Lake Tana and 0.005 to 729.9 in Lake Hayqe, indicating potential low to high ecological risks for aquatic organisms. High ecological risks are particularly evident in fish, daphnia, and algae species exposed to α and β-Endosulfan, DDT, and their metabolites, while specifically in daphnia, endrin poses high ecological risks. The ANOVA test revealed there were statistically significant differences (p-value <0.05) among sampling sites in Lake Tana and the mean values between Lake Tana and Lake Hayqe, underscoring the importance of addressing pesticide-related ecological concerns in the region.